2022
DOI: 10.1167/tvst.11.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Glaucoma Detection and Identification of Novel Diagnostic Areas in Diverse Real-World Datasets

Abstract: Purpose To develop a three-dimensional (3D) deep learning algorithm to detect glaucoma using spectral-domain optical coherence tomography (SD-OCT) optic nerve head (ONH) cube scans and validate its performance on ethnically diverse real-world datasets and on cropped ONH scans. Methods In total, 2461 Cirrus SD-OCT ONH scans of 1012 eyes were obtained from the Glaucoma Clinic Imaging Database at the Byers Eye Institute, Stanford University, from March 2010 to December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…OCT volumetric scans, including ONH-centered and macula-centered ones, can potentially provide more comprehensive features, such as the changes in RNFL, GCIPL, Bruch membrane opening, neuroretinal rim area, the lamina cribrosa, and choroidal. Thus, several studies investigated the potential of 3D DL models in glaucoma detection 48–52. Maetschke et al48 developed a 3D DL model using ONH-centered volumetric OCT scans and compared its performance with 8 kinds of ML classifiers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OCT volumetric scans, including ONH-centered and macula-centered ones, can potentially provide more comprehensive features, such as the changes in RNFL, GCIPL, Bruch membrane opening, neuroretinal rim area, the lamina cribrosa, and choroidal. Thus, several studies investigated the potential of 3D DL models in glaucoma detection 48–52. Maetschke et al48 developed a 3D DL model using ONH-centered volumetric OCT scans and compared its performance with 8 kinds of ML classifiers.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, several studies investigated the potential of 3D DL models in glaucoma detection. [48][49][50][51][52] Maetschke et al 48 developed a 3D DL model using ONH-centered volumetric OCT scans and compared its performance with 8 kinds of ML classifiers. The DLbased approach achieved a peak test AUROC of 0.94, which was substantially higher (P < 0.05) than the best classic ML method (AUROC of 0.89) on segmentationbased features.…”
Section: Oct-based Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volumetric OCT scans, including ONH‐centred and macula‐centred ones, can potentially provide more comprehensive features such as the changes in the RNFL, GCIPL, Bruch's membrane opening, neuro‐retinal rim area, the lamina cribrosa, and choroid. Several studies have shown that DL models based on OCT 3D scans outperformed DL models based on 2D images and also showed non‐inferior performance to glaucoma specialists for detecting glaucomatous structural changes 26–31 …”
Section: Deep Learning In Octmentioning
confidence: 99%
“…Braeu et al reported on a geometric DL model capable of extraction critical structural points from a 3D point cloud of the optic disc and peripapillary region which performed well on two distinct networks with high diagnostic accuracy and was superior to a 3D CNN model, while requiring fewer inputs [17,18]. Noury et al , conversely, identified the lamina cribosa as a region of interest in glaucoma diagnosis [19]. Such geometric models may prove advantageous comparing with class activation maps (CAM)-graded images in the identification of key structural locations within the posterior pole in glaucoma diagnosis and physiology.…”
Section: Detecting Glaucoma With Artificial Intelligence In Different...mentioning
confidence: 99%